ϕ meson production at forward rapidity in Pb–Pb collisions at √sNN=2.76 TeV - Acharya, S.; Torales-Acosta, F.T.; Adamovã, D.; Adolfsson, J.; Aggarwal, M.M.; Aglieri Rinella, G.; Agnello, M.; Agrawal, N.; Ahammed, Z.; Ahn, S.U.; Aiola, S.; Akindinov, A.; et al. (Springer New York LLC, 2018)
φ meson measurements provide insight into strangeness production, which is one of the key observables for the hot medium formed in high-energy heavy-ion collisions. ALICE measured φ production through its decay in muon pairs in Pb–Pb collisions at √sNN = 2.76 TeV in the intermediate transverse momentum range 2 < pT < 5 GeV/c and in the rapidity interval 2.5 < y < 4. The φ yield was measured as a function of the transverse momentum and collision centrality. The nuclear modification factor was obtained as a function of the average number of participating nucleons. Results were compared with the ones obtained via the kaon decay channel in the same pT range at midrapidity. The values of the nuclear modification factor in the two rapidity regions are in agreement within uncertainties.
Keywords: Physics; Rapidity; Nuclear physics; Production (economics); Muon; Nucleon; Strangeness; Particle physics; Meson; Strangeness production; Range (aeronautics); Observable; Baryon; Large Hadron Collider; https://purl.org/pe-repo/ocde/ford#1.03.03